2008
DOI: 10.1097/ta.0b013e318047c07c
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Suppresses Polymorphonuclear Neutrophil Apoptosis After Acute Lung Injury

Abstract: Up-regulation of intrapulmonary COX-2 expression contributes to the suppression of PMN apoptosis after ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A higher number of apoptotic neutrophils in COX-2 deficient mice than COX-1 deficient mice suggested an anti-apoptotic role for COX-2 (37). Jinzhou et al demonstrated that up-regulation of intrapulmonary COX-2 expression contributed to the suppression of polymorphonuclear neutrophil (PMN) apoptosis after acute lung injury (38). Moreover, overexpression of COX-2 was thought to be linked to down regulation of apoptosis in many cell types (39) and played an anti-apoptotic role in human bronchial epithelial cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…A higher number of apoptotic neutrophils in COX-2 deficient mice than COX-1 deficient mice suggested an anti-apoptotic role for COX-2 (37). Jinzhou et al demonstrated that up-regulation of intrapulmonary COX-2 expression contributed to the suppression of polymorphonuclear neutrophil (PMN) apoptosis after acute lung injury (38). Moreover, overexpression of COX-2 was thought to be linked to down regulation of apoptosis in many cell types (39) and played an anti-apoptotic role in human bronchial epithelial cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that iNOS and COX-2 play a critical role in acute lung injury and suppression of iNOS and COX-2 expression protects against sepsis (Speyer et al 2003;Fukunaga et al 2005;Peng et al 2005;Jinzhou et al 2008;Kung et al 2011). To investigate the possible mechanism underlying the protective effect of acacetin in sepsis mice in vivo, we measured the effect of acacetin on iNOS and COX-2 expression in the different treatment groups.…”
Section: The Effect Of Acacetin On Sepsis-induced Inos and Cox-2 Expression In Lung Tissue Of Sepsis Micementioning
confidence: 99%
“…For example, B. bifidum increases the expression of cyclooxygenase-2 (COX-2) (Khailova et al 2010). COX-2 is involved in apoptosis regulation and suppresses neutrophil apoptosis (Jinzhou et al 2008). On the other hand, Lactobacillus significantly increased COX-2 expression in intestinal cells (Otte et al 2008) and this can lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%